Life Cycle Assessment Approach for Tracing the Impact of Recreational Activities in Green Open Spaces, South Tangerang - Indonesia - Luthfia Ainur Rahma; Hermawan, Rachmad; Eva Rachmawati (Media Konservasi, 2025)
South Tangerang has green open spaces currently widely used for community recreation, namely City Park 1 BSD and City Park 2 BSD. Recreational activities can contribute to environmental impacts. Life Cycle Assessment is an approach used to trace the impact of each recreational activity. This research aims to inventory inputs and outputs, calculate the magnitude of emissions based on impact categories, and formulate impact control scenarios for recreational activities in green open space, South Tangerang. The main data collected were the characteristics and activity patterns of visitors. At each recreational activity stage, the input type is identified, and the magnitude of emissions is calculated using the basic formula: Emissions = activity data x emission factor. The next stage is interpreting the results by formulating impact control scenarios. The identified inputs are gasoline and diesel fuel, electrical energy, urine, soap, and organic and inorganic solid waste. Emissions of transportation activities are CO2, N2O, CH4, SO2, and NO2; emissions of organic waste processing are N2O and CH4; emissions of inorganic waste processing are CH4; emissions of electricity use are CO2, SO2, and NO2; as well as emissions of using toilets and soapy water are CH4 and PO43–. Recreational activities in City Park 1 BSD produce greater emissions than in City Park 2 BSD, with hotspots in visitor transportation. Impact control can be carried out using two scenarios: limiting motorized vehicles' use and reducing plastic waste.